The Effect of Self-Efficacy and Work Discipline on Employee Performance through Employee Engagement as Mediation - Utami, Tri; Darmawan, Akhmad; Bagis, Fatmah; Miftahuddin, Muchammad Agung (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effect of Self-efficacy and work discipline on employee performance with Employee Engagement as a mediating variable for employees at the Banyumas Regency Education Office. This research uses quantitative with a saturated sampling approach involving 111 respondents, except structural personnel and operational personnel who are excluded in this study. Data were analyzed using the Structural Equation Modeling - Partial Least Squares 3.0 method. The results showed that Self Efficacy and work discipline have a significant positive effect on employee performance, both directly and through the mediation of Employe Engagement. This research shows the importance of organizations to improve employee confidence, consistency of work discipline, and employee involvement in organizational activities.